Desirable Information of Opioids for Families of Patients With Terminal Cancer: The Bereaved Family Members' Experiences and Recommendations. (April 2017) - Okamoto, Yoshiaki; Tsuneto, Satoru; Morita, Tatsuya; Takagi, Tatsuya; Shimizu, Megumi; Miyashita, Mitsunori; Uejima, Etsuko; Shima, Yasuo
Objective: The aims of this study are to clarify the state of information regarding opioids for families and what kinds of experiences they had with opioids while the patient was followed as an outpatient and inpatient. Participants: This study was part of a cross-sectional nationwide survey of bereaved families of patients with cancer, namely, the Japan Hospice and Palliative Care Evaluation 2 study. The participants in this study comprised 572 bereaved families who had experienced the death of a family member during the period from January 2008 to December 2009 at 1 of 103 certificated palliative care units. Main Outcome Measures: In response to the question of "how much improvement was needed for information regarding opioids, " 41% answered "improvement is not necessary at all, " 43% answered "improvement is slightly necessary, " 14% answered "improvement is necessary, " and 2% answered "improvement is extremely necessary." Regarding anxiety about the use of opioid, it was found that 14% of respondents indicated "opioids are very safe, " 65% of respondents indicated "opioids are relatively safe, " 19% of respondents indicated "opioids are not so safe, " and 2% of respondents indicated "opioids are not so safe at all." from the information obtained for opioids. It was found that 90% of families agreed with the item, "I would like to be clearly explained that drugs for medical purposes are safe and that the patient will not develop a drug addiction and their life expectancy will not be reduced." Conclusion: From this study, it is important for families of patients with cancer to be explained profound and careful information of opioid.